Association of dietary live microbe intake with abdominal aortic calcification in US adults: a cross-sectional study of NHANES 2013–2014 - Huo, Xingwei; Jia, Shanshan; Zhang, Xin; Sun, Lirong; Liu, Xueting; Liu, Lu; Zuo, Xianghao; Chen, Xiaoping (Frontiers in Nutrition, 2023)
Object: To explore the potential association between dietary live microbe intake and abdominal aortic calcification (AAC). Methods: We conducted a cross-section study based on the National Health and Nutrition Examination Survey (NHANES). We categorized the participants into three groups (low, medium, and high dietary intake of live microbes) based on Sanders’s dietary live microbe classification system and participants' 24-hour dietary recall data. AAC was quantified by using dual-energy X-ray absorptiometry (DXA) and diagnosed by using the Kauppila AAC-24 score system. The analyses utilized weighted logistic regression and weighted linear regression. Results: A total of 2586 participants were included. After the full adjustment for covariates, compared to participants with a low dietary live microbe intake, participants with a high dietary live microbe intake had a significantly lower risk of severe AAC (OR: 0.39, 95% CI: 0.22, 0.68, p=0.003), and the AAC score was also significantly decreased (β: -0.53, 95% CI: -0.83, -0.23, p= 0.002). Conclusions: In this study, higher dietary live microbial intake was associated with lower AAC scores and a lower risk of severe AAC. However, more researches are needed to verify it. Keywords: dietary live microbes, abdominal aortic calcification, food–gut-health axis, NHANES, cross-sectional study